Agricultural Credit Guarantee Scheme Funds and Agricultural Performance in Nigeria - Raufu, Mufutau; Fajobi, Deborah Tosin; Dlamini-Mazibuko, Bongiwe; Miftaudeen-Raufu, Abdussalam; Olalere, Jamiu (PT. Riset Press International, 2025)
This study examines the significance of the Agricultural Credit Guarantee Scheme (ACGS) funds in improving agricultural performance in Nigeria. The study uses descriptive statistics and trend analysis to analyze the relationship between ACGS funds and agricultural output in Nigeria, assessing its impact on crop production, livestock, and fishery sectors. The study utilized a quantitative research design to investigate the effect of agricultural credit guarantee scheme funds on agrarian performance in Nigeria. Time series data spanning a period of 41 years (1981-2021) was collected from secondary sources, specifically the National Bureau of Statistics (NBS) and the Central Bank of Nigeria (CBN). The data collected included variables such as gross domestic product (GDP) as a proxy for agricultural performance and the total volume and number of loans issued for cash crops, food crops, and mixed farming as proxies for ACGSF disbursements. This study's findings revealed that Nigeria's Agricultural Credit Guarantee Scheme Fund (ACGSF) has had a significant impact on the agriculture sector, particularly in livestock, crops, and fisheries. The fund experienced a low level of funding before 1999 but increased significantly after the advent of democracy, focusing on agriculture. Livestock and crop production had the highest loan guarantee funding in 2014, while fisheries peaked in 2009. Using the Augmented Dickey-Fuller approach, all variables were found to be stationary at the levels, and some were found to be stationary at the first difference. None of the variables were stationary at the second difference. The estimated F-ratios for Livestock, Crop, and Fishery were 49.71, 190.38, and 122.45, respectively, indicating that the agricultural credit guarantee significantly influences all sectors' output. The adjusted R2 values for Livestock, Crop, and Fishery were 82.97%, 94.67%, and 75.69%, respectively, indicating a good fit for the regression models. The regression results reveal a positive relationship between the GDP of Livestock and cattle and other livestock, with other livestock being significant at the 1% level. The GDP of Fishery also shows a positive significant relationship with ACGSF Fishery. The recommendation is to increase investment in livestock, crop, and fishery sectors to diversify the economy, improve GDP, and reduce dependency on other countries. Loans should be available to qualified individuals as soon as due by participating banks, and more funds should be made available to cash crops and other sectors to earn more foreign exchange. Increased publicity about the scheme is recommended.